Description of the male of Rhoicinus andinus (Araneae, Rhoicininae, Trechaleidae) - Cruz da Silva, Estevam Luís (2007)
The male of Rhoicinus andinus Exline, 1960 is described for the first time, based on two specimens from Cashiari, Camisea River, Cusco, Peru. The genus Rhoicinus has four species recorded from Peru. R. andinus is recognized by having a larger and heavily sclerotized ring at the palpal tibiae. A new geographical distribution for the species is noted.